Cardiac autonomic responses during and after a single session of aerobic exercise with and without blood flow restriction - Julio Cezar Schamne; Adalberto Ferreira Junior; Amanda Cristiane de Araújo; Adriano Eduardo Lima-Silva; Rômulo Cássio de Moraes Bertuzzi; Nilo Massaru Okuno (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: To verify the on and off heart rate (HR) and HR variability (HRV) kinetics during a high-load aerobic exercise and a low-load aerobic exercise, with and without blood flow restriction (BFR). Methods: Fourteen healthy male subjects performed three randomly assigned experimental sessions: 1) 10 minutes walking at 40% of maximal aerobic speed (MAS) (40LL); 2) 10 minutes walking at 40% of MAS with BFR (40LL+BFR); and 3) 10 minutes running at 70% of MAS (70HL). The HR and HRV measurements were taken at rest, during exercise and the recovery period after constant load sessions. Results: The HR on- and off- kinetics, and HRV on-kinetics were faster in 40LL than in 40LL +BFR and 70HL (p < 0.05). The time constant (τon) of HR on-kinetics was faster in 40LL+BFR than in 70HL (23.4 ± 9.5 s vs 42 ± 9.5 s, respectively, p < 0.01), and was accompanied by faster HRV on-kinetics (12.4 ± 9.6 s vs 20.3 ± 13.7 s, respectively, p < 0.01). Although HR off-kinetics was not different between 40LL+BFR and 70HL, the recovery of time and frequency HRV indices were delayed in 70HL when compared to 40LL and 40LL+BFR (p < 0.05). Conclusions: These findings indicate that 40LL promoted faster cardiac adjustments compared to 40LL+BFR and 70HL sessions. Additionally, 40LL+BFR promoted faster cardiac adjustment and better HRV recovery compared to the 70HL session.